استعداد طالبات كلية الإمام الشافعي بمحافضة بجمبر لمواجهة الدور المزدوج بين الحياة الزوجية والمجال المهني: دراسة من منظور فقه الأسرة: The Readiness of Final-Year Students at Imam Al-Shāfi‘ī College Jember in Facing Dual Roles Between Marriage and Work: A Family Jurisprudence Perspective - Nadia Aulia Ramanda Putri; Sabilul Muhtadin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2026)
In the era of globalization, women’s participation in the labor market has become a common phenomenon, including among final-year female students preparing for family life alongside a professional career. This study aims to analyze the readiness of final-year female students at Imam Syafi’i College in Jember to face dual roles in the future. The study employs a combination of field research and normative analysis based on Islamic family law using a qualitative descriptive approach. Data were collected through in-depth interviews and direct observation involving five unmarried students and were analyzed based on the Qur’an, Sunnah, and applicable regulations, including Islamic law and Marriage Law No. 1 of 1974. The results indicate that the participants possess an adequate level of awareness as well as intellectual and psychological readiness to perform their future roles as wives and mothers while participating in professional activities. Understanding Islamic legal rulings regarding women’s employment is essential for balancing family responsibilities and public roles. The study confirms that women’s employment is permissible as long as it complies with Islamic principles and does not lead to the neglect of family responsibilities.